What are our children eating? Children's nutrition knowledge and the relationship between nutritional intake and attention. [article]. - Barra, Louella L. .
The study looked into knowledge of an attitudes towards nutrition and the eating practices and food preferences of a sample of a Grade I students. It also sought to explore a possible relationship between what these students were eating and there ability to concentrate on a given task. The study had two parts: the first part described what the Grade I pupils already knew about the nutrition, their views of different eating practices and their food habits; the second part looked into the relationships between variables such as family background, nutritional intake, nutrition knowledge, attitude and practices and the child's ability to concentrate on an activity on hand. Participants were found to be well informed on various nutritional recommendations for good health. these general knowledge in turn appeared to influence their food habits, food preferences and attitudes about certain foods. The study also correlated family background variables with the participant's score in nutrition knowledge, auditory attention and visual alertness task.